The IMPLEMENTATION OF SETTLEMENT OF FAILURE TO PAY BY CAR LOAN CUSTOMERS AT BCA FINANCE SURABAYA KLAMPIS BRANCH - Rachmadiani, Emma; Maharani, Sri (JARES (Journal of Academic Research and Sciences), 2024)
This study aims to determine the settlement of defaults that have been made by car loans customers at PT. BCA Finance Surabaya Klampis Branch. This research uses an empirical research type and the data source is obtained from the results of interviews with Credit Marketing Officer PT. BCA Finance Surabaya Klampis Branch, literature, and laws regulations. The method of collecting data from this study was obtained by interviews, literature studies, and observation. The data analysis method used in this study is a qualitative approach, the information obtained is in the form of statements and written materials. The results of this study can be concluded that; (1) The settlement of default by car loans customers at PT. BCA Finance Surabaya Klampis Branch is conducted in a non-litigation (2) handled specifically by the ASR department which is responsible for maintaining non-performing, (3) by providing various services with the aim that customers who have defaulted continue to pay their obligations. (4) If the customer still does not fulfill his obligations, then the vehicle is forcibly withdrawn by PT. BCA Finance Surabaya Klampis Branch.